Measuring institutional competitiveness in Europe - Stefan Huemer; Beatrice Scheubel; Florian Walch (European Central Bank (ECB), 2013)
While there are many methods to measure the competitiveness of an economy, most of these concepts ignore the fact that competitiveness can change because of market processes like wage negotiation but also because of political decision-making. Governments that compete with others for factors of production face the incentive to adjust key policy variables to improve their competitive position. Disentangling market-induced and politics-induced changes in competitiveness is not easy, but strongly warranted given current discussions that some EMU Member States should improve their competitive position within the euro area by adjusting policy variables. Increasing country competitiveness is one of the key objectives currently discussed by policy makers in the context of creating an economic union in the euro area, to complement monetary union. We propose a new competitiveness index that captures the dimensions in which politics can influence competitiveness beyond factor price adjustments. Our index shows that the individual components of institutional competitiveness have developed heterogeneously among EMU Member States. To explain these divergent developments, the uneven integration within the EU Single Market may play a role.
Keywords: E02; E44; F15; H11; N44; 330; competitiveness; Fiscal Policy; institutional competitiveness index